The use of natural products in Latin America and the Caribbean for blocking dengue infection in mosquito cells - Golding, Mario A. J.; Khouri, Nadia K.; Anderson, Kathryn B.; Wood, Troy D.; Sandiford, Simone L. (Frontiers in Virology, 2023)
Latin America and the Caribbean continue to be adversely affected by dengue with the disease being endemic in several countries in this region. As a result, the social and economic impacts of the disease have risen significantly. Currently, there are very few solutions available to limit the spread of the virus, with vector control being the most commonly used. However, due to increased insecticidal resistance, scientists in the region have actively been seeking new ways to limit the spread of the virus. This quest has led researchers to investigate the antiviral properties of natural products. While antiviral screening activities focused on preventing or treating infection of the human host remains a significant area of study, some scientists have now focused their attention on preventing infection or transmission in the mosquito vector. This review therefore aims to highlight the use of natural products in Latin America and the Caribbean for blocking viral transmission of dengue virus in mosquitoes. This novel approach is promising and could ultimately be used in conjunction with other methods to help significantly reduce dengue incidence in the region.